Light-induced color changes and chemical modification of treated and untreated chestnut wood surface. (March 2015) - Calienno, Luca; Pelosi, Claudia; Picchio, Rodolfo; Agresti, Giorgia; Santamaria, Ulderico; Balletti, Federica; Monaco, Angela Lo
Abstract : The aim of this work is to study the surface modifications of chestnut ( Castanea sativa Mill.) wood by reflectance spectrophotometry and Fourier transform infrared spectroscopy (FTIR) in order to understand the mechanisms that cause changes and to suggest possible solutions to avoid degradation phenomena. The experimental data were statistically treated to evaluate their significance. Concerning the surface protection of wood, starting from the results obtained by testing different commercial products, attention was focused on a novel organic preservative/consolidant product (Linfoil ® ) that has attracted great interest in the field of conservation of wooden artifacts. Color monitoring showed that wood surface color undergoes an important variation due to photoirradiation, occurring within the first 24 hours and mainly due to L* decrease and b* increase. Though the protective treatment modifies wood color, nevertheless the product tested seems to protect the wood surface by reducing photoyellowing. FTIR analysis indicated that irradiation caused the degradation of lignin and increased the concentration of the chromophore groups on the wood surface. Changes in the chromaticity coordinates can be linked to the degradation of lignin and to increase of the concentration of carbonyl groups.